2022
DOI: 10.1016/j.gocm.2022.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Intimate hygiene practices and reproductive tract infections: A systematic review

Abstract: IntroductionWorldwide, women perform a variety of vaginal practices to enhance their intimate hygiene and sexual health.ObjectiveTo conduct a systematic review to assess the different kinds of intimate hygiene practices and their association with reproductive tract infections and complications.MethodsPubMed, Medline and The Cochrane Library were used. Both observational and interventional studies targeting the urogenital infections and their association with hygiene practices were included. Exclusion criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Most women using reusable menstrual pads appropriately cleaned them, and there was no difference in symptom prevalence among participants using disposable compared to clean reusable pads. This finding contrasts with previous research which has found urogenital infections were more common in women using reusable materials compared to disposable pads [ 10 , 17 – 23 , 30 , 33 ], however, these studies did not differentiate between improvised reusables and reusable pads. These findings are particularly important in the context of increasing uptake of commercially produced reusable menstrual pads as a cost- and environmentally sustainable alternative to disposable pads.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Most women using reusable menstrual pads appropriately cleaned them, and there was no difference in symptom prevalence among participants using disposable compared to clean reusable pads. This finding contrasts with previous research which has found urogenital infections were more common in women using reusable materials compared to disposable pads [ 10 , 17 – 23 , 30 , 33 ], however, these studies did not differentiate between improvised reusables and reusable pads. These findings are particularly important in the context of increasing uptake of commercially produced reusable menstrual pads as a cost- and environmentally sustainable alternative to disposable pads.…”
Section: Discussioncontrasting
confidence: 98%
“…Menstrual hygiene practices investigated for their association with urogenital symptoms in past studies were reviewed to inform the variables included and constructed for this study [10,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. A full list of questions used in this study are presented in S1 Table in S1 File.…”
Section: Construction Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…IVP causes changes to vaginal flora resulting in increased risk of STIs/BV including HIV. A recent systematic review found that IVP increased the risk of vaginal infections (BV, TV and vulvovaginal candidiasis),40 two others found no association between IVP and TV15 or BV 41. One study in South Africa found that IVP was associated with increased risk of HIV infection but not other STIs 42.…”
Section: Discussionmentioning
confidence: 99%
“…Physical health outcomes will include symptoms of urogenital infection or irritation, and healthcare seeking for menstrual pain or disorders. Menstrual hygiene practices and genital care have been linked to reproductive tract irritation and infection 57. Girls will be asked to self-report symptoms of urogenital infection including itching and burning, pain on urination, frequent urination, genital odour and abnormal vaginal discharge.…”
Section: Methods and Analysismentioning
confidence: 99%